The Effect of Understanding and Religiosity on MSME Taxpayer Compliance in Paying Tax PP 23 Year 2018 - Faridzi, Muhammad Aldi; Suryanto, Tulus; Devi, Yulistia (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2022)
The purpose of this study was to determine whether the influence of the level of understanding and religiosity had a partial and simultaneous effect on MSME taxpayer compliance in paying tax PP 23 TH 2018 in Sukarame District, Bandar Lampung City. This research uses quantitative methods with the type of field research. This study uses multiple linear regression analysis method using SPSS version 25 program. Based on the results of data analysis, it can be concluded that understanding and religiosity have a partial and simultaneous effect on MSME taxpayer compliance in paying tax PP 23 TH 2018. Limitations of this study namely on the object of observation that focuses on MSMEs so that it opens up opportunities for further researchers to add wider objects. Income Implications for MSMEs is one of the businesses that is taxed based on PP no. 23 of 2018 with a lower rate of 0.5%. This PP regulates taxpayers who have a gross turnover of not more than 4,800,000,000 for final income tax of 0.5% replacing the previous rate of 1% of monthly turnover.